Enzymatic production of biodiesel from insect fat using methyl acetate as an acyl acceptor: Optimization by using response surface methodology. (15th February 2018) - Nguyen, Hoang Chinh; Liang, Shih-Hsiang; Chen, Shang-Sian; Su, Chia-Hung; Lin, Jhih-Huei; Chien, Chien-Chung
Graphical abstract: Highlights: An enzymatic interesterification of insect fat with methyl acetate was successfully developed for biodiesel production. Methyl acetate had no negative effect on enzyme activity and increased biodiesel yield. The reaction conditions were optimized using response surface methodology. Novozym 435 was efficiently reused for the reaction. All the analyzed properties of black soldier fly larvae biodiesel met the standard EN 14214. Abstract: Black soldier fly larvae (BSFL) are oleaginous insects that can assimilate organic waste for fat accumulation, and thus serve as an alternative feedstock for biodiesel production. In lipase-catalyzed transesterification, enzymes are deactivated by excess methanol. To address this obstacle, methyl acetate is suggested as an alternative acyl acceptor to methanol. In this study, methyl acetate was first used in the enzymatic production of biodiesel with BSFL as a triglyceride source. The interesterification of BSFL fat with methyl acetate was catalyzed using Novozym 435 as an efficient immobilized lipase. Response surface methodology was used to optimize the reaction and establish a reliable mathematical model for prediction. A maximum biodiesel yield of 96.97% was reached at a reaction time of 12 h, molar ratio of methyl acetate to fat of 14.64: 1, enzyme loading of 17.58%, and temperature of 39.5 °C. Under these optimal reaction conditions, Novozym 435 could be reused for up to 20 cycles without loss in enzyme activity. The properties of BSFL biodiesel were also investigated and all met the European standard EN 14214. This study indicates that the enzymatic interesterification of BSFL fat with methyl acetate is a promising and ecofriendly method for green fuel production.